Silver nanoparticles adsorption by the synthetic and natural adsorbent materials : an exclusive review - Achmad, Syafiuddin; Mohamad Ali, Fulazzaky; Salmiati, Salmiati; Ahmad Kueh, Beng Hong; Mohammad, Fulazzaky; Mohd Razman, Salim (Springer Nature Switzerland AG, 2020)
Silver nanoparticles (AgNPs) have been used in a wide range of industrial products. The release of AgNPs as antimicrobial agent into the river or lake can raise the ecological concern because they have been proven to be associated with toxicity of the aquatic animals. An exclusive review of AgNPs adsorbed by the various synthetic and natural adsorbent materials is important to understand the behaviour of AgNPs in the complex environmental conditions. The transformation of AgNPs into various forms in an aquatic environment depends on the physical, chemical, and biological characteristics of water. Many types of natural materials can be used to fabricate the adsorbents because pore structure, surface area, and active sites of functional groups of the adsorbent can be developed during the carbonisation and activation stages. The mass transfer factor and modifed mass transfer factor models would be considered tools that can be used to describe the mechanism and kinetics of AgNPs adsorption onto the natural adsorbents infuenced by the electrostatic and van der Waals forces. This exclusive review provides the valuable insights into future challenges of AgNPs adsorption to contribute to sustainable improvement in the management of aquatic ecosystems.